The Geopolitics of Knowledge Production in Applied English Language Studies: Transknowledging and a Two-Eyed Critical Southern Decoloniality - Chaka, Chaka (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
This paper mapped out and explored the geopolitics of knowledge production in applied English language studies (AELS). It did so by employing a double judgmental sampling and by investigating four composite factors in volume 42 of the journal Applied Linguistics (AL), which comprised six issues and forty-three articles, as published in 2021. These composite factors were nationalities and institutional affiliations of the editor, the associate editors, the editorial board, and the international advisory board; nationalities and institutional affiliations of publishing or contributing authors; the foci of the published articles; and the theoretical framings and epistemic orientations of the published articles. The paper maintains that these composite factors serve as important axes of epistemic production practices and as critical loci of knowledge circulation for AELS in this journal. AL has occupied the first quartile (Q1) in communication, and in linguistics and language since 1999 as ranked by both Scopus and Resurchify. As such, it is a top-tier journal in the field of AELS or of applied linguistics. Based on its analysis, one of the arguments the paper makes is that individually and collectively these composite factors function, simultaneously, as a gate-keeping mechanism for knowledge production and as a validation, legitimation, and arbitration mechanism for knowledge production in AL. The paper has also established that there is an invisibilization of the Global South authors in these six issues of AL. This factor, the paper contends, is attributable to the geopoliticizing of knowledge production in these AL’s issues. Lastly and importantly, the paper advocates transknowledging and a two-eyed critical Southern decoloniality for AELS, and draws a link between this two-pronged theoretical framing and transepistemic language education.